Rigid-flexible contact analysis of an inflated membrane balloon with various contact conditions. (July 2018) - Liu, M.X.; Wang, C.G.; Li, X.D.
Highlights: Decoupled governing equations are obtained based on the force balance relationship. Various contact conditions, especially the harmonic one, are discussed. The numerical results from no-slip condition are verified by the designed test (DIC technology). The maximum ordinate difference appears in the intersection of meridian stretch ratio. The no-slip condition results in the maximum volume and minimum internal pressure. Abstract: Considering the Mooney–Rivlin hyperelastic model, a semi-analytical approach is introduced to analyze the rigid–flexible contact behaviors of an inflated membrane balloon between two plates with various interface conditions. This approach is based on the differential formulation and the coupling property of equilibrium equations are well-solved. In order to verify the reliability of the proposed theoretical model, an experimental test is designed, by which some important contact characteristics and patterns (no-slip condition) are obtained. Two special phenomena are observed for the meridian stretch ratio with different friction coefficients. One is that the intersection points of all curves fall in a small interval and the intersection of any two curves represents the same changing rate of the horizontal ordinate, resulting in the maximum difference. The other is the dividing point, where the stretch ratio decreases on the left of it and increases on the right due to the introduction of friction. Under the same contact angle, the larger displacement load should be applied to the balloon for the small friction coefficient condition, resulting in the smaller contact area and internal pressure. In addition, the vulnerable position, direction and contact condition of the balloon are found during the contact process, which happen in the center along the circumferential direction under no-slip condition. These results provide solid guidance and support for our understanding of the rigid-flexible contact behaviors of an inflated membrane balloon. Graphical abstract: